2019
DOI: 10.1097/bsd.0000000000000721
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific Rods for Surgical Correction of Sagittal Imbalance in Adults

Abstract: Study Design: This was an innovative concept and a preliminary prospective series. Objective: The aim of this study was to present the concept and the technical aspects of patient-specific rods (PSR), and compare preoperative and postoperative sagittal parameters (after PSR implantation), with a special focus on the difference pelvic incidence (PI)—lumbar lordosis (LL). Background: Despite established techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
4
25
1
Order By: Relevance
“…Finally, results from our study revealed a low rate of mechanical complications (4%) without rod breakage which is comparable with previous report [ 9 ]; however, our mechanical results must be taken into account cautiously due to the short follow-up (3 months).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, results from our study revealed a low rate of mechanical complications (4%) without rod breakage which is comparable with previous report [ 9 ]; however, our mechanical results must be taken into account cautiously due to the short follow-up (3 months).…”
Section: Discussionsupporting
confidence: 91%
“…The results presented here are in line with the study of Barton et al [ 8 ] who also reported significant improvement of sagittal parameters using PSR. More recently, Solla et al [ 9 ] reported their experience about 60 patients managed using PSR with a correction of PI-LL mismatch in 66% of the cases, a correction of SVA in 38% of the cases, and a correction of PT in 29% of the cases. According to their results, postoperative PI-LL mismatch was correlated with preoperative PI-LL and performing a PSO; postoperative SVA was correlated with preoperative SVA, performing a PSO, and age of the patient, and postoperative PT was correlated with preoperative PT.…”
Section: Discussionmentioning
confidence: 99%
“…The notion of age-adjusted parameters emphasizes that PI–LL mismatch may change substantially for patients over 74 years old [28]. New technology using the latest advancements in machine learning and predictive analytics may offer substantial clinical advantages in determining unique goals of correction to reduce the rates of pseudarthrosis, revision surgery, and proximal junctional failure [41, 42, 45].…”
Section: Resultsmentioning
confidence: 99%
“…Improved means of rod contouring are needed, and the recent introduction of preplanned ma-chine-bent rods may improve fatigue life, thereby extending the time for arthrodesis to occur. 84 In addition, preplanned rods may facilitate achievement of desired spinal alignment which may also enhance fatigue life. Advances are also needed in osteobiologics and other grafting materials in order to improve fusion rates.…”
Section: Advances To Further Reduce Complicationsmentioning
confidence: 99%
“…Preplanned machine-bent rods may reduce junctional failures by helping to ensure that desired alignment corrections are achieved, including overall magnitudes of thoracic and lumbar curves, location of LL restoration (e.g., in the lower lumbar levels), and appropriate contouring of the proximal end of the rod. 34,35,84 An overall better definition of individualized alignment objectives, beyond simple age-adjusted objectives, could markedly reduce PJK. 32,36 In the future, more aggressive attention to bone optimization may also reduce junctional fractures.…”
Section: Advances To Further Reduce Complicationsmentioning
confidence: 99%